Fees for municipal waste as an economic tool for reducing the amount of mixed municipal waste - Mihaliková, Eva (Bulletin of Geography. Socio-economic Series, 2025)
One of the key tools of environmental policy is economic instruments. This article focuses on one type of economic instrument applied in waste management – namely, fees for municipal waste. The aim of this work is to ascertain the amount of mixed municipal waste produced, analyze the level of fees for municipal waste, and determine the type of fee applied in Slovakia and its individual regions. This work underscores the need to implement volume-based waste fees and indicates the potential of artificial intelligence which, by employing smart bins and sensors, can assist in determining the quantity and type of waste. This could form the basis for calculating volume-based fees and establishing a more equitable waste-charging system.